Evolving human resource dimension in Indonesia's digital public relations landscape - Ivan Bimantoro Wachid; Maulina Pia Wulandari; Zulkarnain Nasution (Jurnal Studi Komunikasi, 2024)
The advancement of technology has transformed the field of public relations in Indonesia, requiring a change in the human resources management to effectively implement digital PR strategies. This study investigates the changing skills and abilities that Indonesian PR professionals require by conducting detailed interviews with five prominent Indonesian public relations practitioners. The results emphasise crucial competencies such as strategic planning, media relations, crisis management, and digital proficiencies. The crucial role of PR associations in directing the future of digital PR through diverse tactics and training programs is also highlighted. This study asserts that the ongoing improvement of digital literacy and strategic abilities is essential. Organisations should establish extensive training programs and cultivate collaborations with professional associations to offer important resources and guarantee competitiveness in the digital era. These endeavours are crucial for promoting and enhancing digital public relations strategies and bolstering organisational communication and reputation in Indonesia.